Targets for pollutants in rat and human pancreatic beta-cells: The effect of prolonged exposure to sub-lethal concentrations of hexachlorocyclohexane isomers on the expression of function- and survival-related proteins - Pavlíková, Nela; Šrámek, Jan; Jaček, Martin; Kovář, Jan; Němcová, Vlasta (Environmental toxicology and pharmacology, 2023)
Decades after most countries banned hexachlorocyclohexane, HCH isomers still pollute the environment. Many studies described HCH as a pro-diabetic factor; nevertheless, the effect of HCH isomers on pancreatic beta-cells remains unexplored. This study investigated the effects of a one-month exposure to α-HCH, β-HCH, and γ-HCH on protein expression in human (NES2Y) and rat (INS1E) pancreatic beta-cell lines. α-HCH and γ-HCH increased proinsulin and insulin levels in INS1E cells, while β-HCH showed the opposite trend. α-HCH altered the expression of PKA, ATF3, and PLIN2. β-HCH affected the expression of GLUT1, GLUT2, PKA, ATF3, p-eIF2α, ATP-CL, and PLIN2. γ-HCH altered the expression of PKA, ATF3, PLIN2, PLIN5, and IDH1. From the tested proteins, PKA, ATF3, and PLIN-2 were the most sensitive to HCH exposure and have the potential to be used as biomarkers.
Keywords: hexachlorcyklohexan; látky znečišťující životní prostředí; Rats; Diabetes; Perilipin-2; Environmental Pollutants; Animals; Beta-cells; Humans; krysa rodu Rattus; Hexachlorocyclohexane; isomerie; Isomerism; lidé; Insulin; zvířata; ATP citrate lyase